2016
DOI: 10.1111/1754-9485.12502
|View full text |Cite
|
Sign up to set email alerts
|

FAST MRI breast screening revisited

Abstract: Given the absence of statistically significant difference in the FPR and recall rates in comparison with FD, FAST scans can replace FD for screening of breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
24
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 6 publications
3
24
0
Order By: Relevance
“…The abbreviated breast MRI protocol is an excellent solution for these issues. Our study confirms prior findings which show that using an abbreviated protocol performs similar to a full MRI protocol for lesion detection and can be used as a less costly and faster alternative to supplemental screening.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The abbreviated breast MRI protocol is an excellent solution for these issues. Our study confirms prior findings which show that using an abbreviated protocol performs similar to a full MRI protocol for lesion detection and can be used as a less costly and faster alternative to supplemental screening.…”
Section: Discussionsupporting
confidence: 90%
“…[18][19][20][21][22] which show that using an abbreviated protocol performsF I G U R E 2 Cancers detected by all five readers on post-contrast T1-weighted dynamic images [Color figure can be viewed at wileyonlinelibrary.com] F I G U R E 3 Maximum intensity projection (MIP) images showing the cancers detected by all five readers [Color figure can be viewed at wileyonlinelibrary.com] TA B L E 3 Details of the seven cancers including 3 y outcome Cancer undetected by two readers. Maximum intensity projection (MIP) image (A) and a subtraction image (B) on the bottom showing linear subtle clumped enhancement.…”
mentioning
confidence: 99%
“…To improve access, tolerance, and reduce cost, Kuhl and colleagues [112] introduced the ultrafast, 3-min, breast MRI for screening and demonstrated that abbreviated breast MRI maintained comparable sensitivity and specificity to the full diagnostic protocol. Table 3 summarizes results of abbreviated MRI to date [112][113][114][115][116][117]. Incremental cancer detection rate following abbreviated screening breast MRI ranges between 8.9 and 36.5 cancers per 1000 screens.…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…AB-MRI reduces the MRI examination and interpretation time and allows faster throughput, leading to reduced cost and increased availability of breast MRI screening to intermediate-risk women (1,(4)(5)(6). In several studies involving different populations, AB-MRI screening has consistently shown cancer detection rates and diagnostic accuracy comparable to those of FD-MRI (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18). AB-MRI with first postcontrast images preferentially detects invasive cancers and high-grade ductal carcinoma in situ (DCIS) due to their neoangiogenesis and rapid wash-in of contrast compared with fibrocystic change and low-grade DCIS (7).…”
Section: Study Populationmentioning
confidence: 99%